Kesesuaian Genotipe Kedelai untuk Tanaman Sela di Bawah Tegakan Pohon Karet - Sundari, Titik; Purwantoro, Purwantoro (Jurnal Penelitian Pertanian Tanaman Pangan, 2014)
This research was aimed to identify shade-tolerant soybean genotypes that was suitable for planting under rubber tree plantation. The research was conducted at three locations of rubber tree plantation in Central and East Lampung where the rubber tree were at age of 3 to 4 years, during dry season of 2011. The materials consisted of 30 soybean genotypes, where 23 lines were shadetolerant, and seven were as check varieties (Pangrango, Burangrang, Malabar, Argomulyo, Grobogan, Ijen, and Tanggamus). Each genotype was planted in plot of 4 m x 2.2 m, plant spacing was 40 cm x 15 cm, two plants /hill. The experiment used a randomized block design, repeated four times. Before planting, dolomite of 1.5 t/ha was applied, and 75 kg Urea / ha + 100 SP36 kg/ha + 100 kg KCl /ha was applied at planting time. Observations were done on flowering date, harvesting date, plant height, number of branches, number of reproductive nodes, number of pods, seed weight per plant and grain yield. The light intensity under the rubber tree canopy was observed every week after the soybean age was 30 days (DAP), at 11:00 to 12:00 pm. The levels of shade made by the rubber tree canopy at three locations were different; at Tulangbalak (East Lampung) and Gunungsari (Central Lampung) ranged between 20% to 40%, at Gunungadi (Central Lampung) between 40% to 60%. Genotypes IBM22-861-2-22-3-1 and AI26-1114-8-28-1-2 yielded consistently well in two locations, in East Lampung (1.40 t/ha and 1.43 t/ha), in Central Lampung (1.19 t/ha and 1.18 t/ha). Genotype IBM22-861-2-22-3-1 and AI26-1114-8-28-1-2 produced the highest average yield out of the three locations, i.e 1.13 t/ha. Genotype IBM22-861-2-22-3-1 and AI26-1114-8-28-1-2 were considered as suitable genotypes for planting under the rubber tree of 3 to 4 years of age.